Automated quantification of the landing error scoring system with a markerless motion-capture system - Mauntel, T. C.; Padua, D. A.; Stanley, L. E.; Frank, B. S.; DiStefano, L. S.; Peck, K. Y.; Cameron, K. L.; Marshall, S. W. (Journal of Athletic Training, 2017)
Context: The Landing Error Scoring System (LESS) can be used to identify individuals with an elevated risk of lower extremity injury. The limitation of the LESS is that raters identify movement errors from video replay, which is time-consuming and, therefore, may limit its use by clinicians. A markerless motion-capture system may be capable of automating LESS scoring, thereby removing this obstacle.